Age-dependent variation in cytokines, chemokines and biologic analytes rinsed from the surface of healthy human skin - Kinn, Patrick M.; Holdren, Grant O.; Westermeyer, Brittney A.; Abuissa, Mousa; Fischer, Carol L.; Fairley, Janet A.; Brogden, Kim A.; Brogden, Nicole K. (Scientific reports, 2015)
In the skin, aging is associated with overall epidermal thinning, decreased barrier function and gradual deterioration of the epidermal immune response. However, the presence and role of cytokines, chemokines and biologic analytes (CCBAs) in immunosenescence are not known. Here we identified age-related changes in skin properties and CCBAs from stratum corneum of healthy human subjects, providing a means to utilize CCBAs as benchmarks for aging skin health. Transepidermal water loss and a(*) (skin redness) decreased in an age-dependent manner and were significantly lower (p < 0.05) in Groups 2 (56.6 ± 4.6 years) and 3 (72.9 ± 3.0 years) vs. Group 1 (24.3 ± 2.8 years). In skin wash fluid, 48 CCBAs were detected; seven were significantly lower (p < 0.05) in Groups 2 and 3: EGF, FGF-2, IFNα2, IL-1RA, HSA, keratin-6 and involucrin; cortisol was significantly higher (p < 0.05) in Groups 2 and 3. Our results correspond with the pro-inflammatory shift that occurs with immunosenescence and also provides basis for understanding the inflammatory changes in normal aging skin.